PENYULUHAN PRODUK DAN LAYANAN PERBANKAN DI ERA DIGITAL BAGI SISWA SMA SENTOSA JAKARTA BARAT DAN MAHASISWA STIE WIYATAMANDALA - Suroso Suroso (Jurnal Abdi Mandala, 2022)
Bank is an institution that has an intermediary role or as an intermediary between parties with excess funds (surplus spending units) and parties with shortages of funds (deficit spending units) which indirectly helps the circulation of money in society. In order to remain able to carry out this role, public confidence in the bank's performance is needed. Migration to digital will be a challenge for changing the environment when economic actors and the public do not fully understand how to conduct economic transactions and choose digital banking. The outputs that will be produced are educational solutions and informative outreach to the community by collaborating with media partners. In this context, the role of technology in turning banks into digital banking is expected to change the mindset of the behavior of customers and bank employees in transacting from conventional to digital.